Comprehensive Characterization of the Genomic Landscape in Chinese Pulmonary Neuroendocrine Tumors Reveals Prognostic and Therapeutic Markers (CSWOG-1901). (4th February 2022) - Peng, Wenying; Cao, Liming; Chen, Likun; Lin, Gen; Zhu, Bo; Hu, Xiaohua; Lin, Yingcheng; Zhang, Sheng; Jiang, Meilin; Wang, Jingyi; Li, Junjun; Li, Chao; et al.
Abstract: Background: Pulmonary neuroendocrine tumors (pNETs) include typical carcinoid (TC), atypical carcinoid (AC), large cell neuroendocrine carcinoma (LCNEC), and small cell lung carcinoma (SCLC). The optimal treatment strategy for each subtype remains elusive, partly due to the lack of comprehensive understanding of their molecular features. We aimed to explore differential genomic signatures in pNET subtypes and identify potential prognostic and therapeutic biomarkers. Methods: We investigated genomic profiles of 57 LCNECs, 49 SCLCs, 18 TCs, and 24 ACs by sequencing tumor tissues with a 520-gene panel and explored the associations between genomic features and prognosis. Results: Both LCNEC and SCLC displayed higher mutation rates for TP53, PRKDC, SPTA1, NOTCH1, NOTCH2, and PTPRD than TC and AC. Small cell lung carcinoma harbored more frequent co-alterations in TP53 - RB1, alterations in PIK3CA and SOX2, and mutations in HIF-1, VEGF and Notch pathways. Large cell neuroendocrine carcinoma (12.7 mutations/Mb) and SCLC (11.9 mutations/Mb) showed higher tumor mutational burdens than TC (2.4 mutations/Mb) and AC (7.1 mutations/Mb). 26.3% of LCNECs and 20.8% of ACs harbored alterations in classical non-small cell lung cancer driver genes. The presence of alterations in the homologous recombination pathway predicted longer progression-free survival in advanced LCNEC patients with systemic therapy ( P = .005) and longer overall survival (OS) in SCLC patients with resection ( P = .011). The presence of alterations in VEGF ( P = .048) and estrogen ( P = .018) signaling pathways both correlated with better OS in patients with resected SCLC. Conclusion: We performed a comprehensive genomic investigation on 4 pNET subtypes in the Chinese population. Our data revealed distinctive genomic signatures in subtypes and provided new insights into the prognostic and therapeutic stratification of pNETs. Abstract : The optimal treatment strategy for different subtypes of pulmonary neuroendocrine tumors (pNET) remains elusive, partly because of a lack of understanding of their molecular features. This article explores differential genomic signatures in pNET subtypes and potential prognostic and therapeutic biomarkers.